2007
DOI: 10.1111/j.1467-9841.2007.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Legal discourse and the cultural intelligiblity of gendered meanings1

Abstract: This paper considers the methodological challenges that 'post-modern' approaches to gender (Cameron 2005) pose for the field of language and gender. If we assume that gender cannot be 'read off' the identities of speakers, but rather is a social process by which individuals come to make cultural sense, then how do we best investigate this process? As Stokoe (2005) and Stokoe and Smithson (2002) have argued, it is problematic within such frameworks to conduct research that pre-categorizes individuals as women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 38 publications
(43 reference statements)
1
38
0
5
Order By: Relevance
“…The idea that gendered ideologies are at play when adjudicators decide between conflicting stories in the courtroom is also evident in the work of Ehrlich (2007). Ehrlich analyzed both the trial proceedings and the judicial opinions of a 1995 Canadian rape trial, Her Majesty the Queen v. Ewanchuk, where two lower courts acquitted the accused of sexual assault, after which the Supreme Court of Canada overturned this acquittal and convicted the accused.…”
Section: Determining the "Official Story": Truth Plausibility And Imentioning
confidence: 99%
See 2 more Smart Citations
“…The idea that gendered ideologies are at play when adjudicators decide between conflicting stories in the courtroom is also evident in the work of Ehrlich (2007). Ehrlich analyzed both the trial proceedings and the judicial opinions of a 1995 Canadian rape trial, Her Majesty the Queen v. Ewanchuk, where two lower courts acquitted the accused of sexual assault, after which the Supreme Court of Canada overturned this acquittal and convicted the accused.…”
Section: Determining the "Official Story": Truth Plausibility And Imentioning
confidence: 99%
“…But what kind of cultural sensemaking framework equates passivity with consent? Ehrlich (2007) argued that culturally normative ideas about women's passive, acquiescing sexuality seemed to be in play when the lower courts ruled that a woman who is emotionless and "frozen" in her demeanor implies consent. In other words, the trial judge and the Alberta Court of Appeal judges seemed to view sexual passivity as appropriately feminine and, as a result, what the complainant described as submitting to sex out of fear became intelligible to these courts as consenting to sex, or at the least, implying consent to the perpetrator.…”
Section: Determining the "Official Story": Truth Plausibility And Imentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has shown, both in adversarial (e.g., Matoesian, 2001;Ehrlich 2007) and inquisitorial legal systems (e.g., Sneijder 2011, Van der Houwen 2013, that the prevailing "referentialist" linguistic ideology (which holds that the meaning of quoted discourse exclusively resides "inside the words" of the quoted text) entirely draws out of sight the strategic recontextualizations which this text is subject to as it is incorporated in the speaker's new discourse. Direct reported speech, in which the speaker at first sight merely "animates" (Goffman 1981) what another speaker presumably said, thus allows legal actors to subtly fuse the quoted discourse with their own voice-which is why it constitutes such a powerful rhetorical device.…”
Section: The Presumed Invisibility Of Reporting Agentsmentioning
confidence: 99%
“…The assumption that a document quoted in court is a stable entity "hides the diachronic instability of the discourse from which text emerged" (Rock et al, 2013: 3). Throughout the various nodes of the legalbureaucratic trajectory of a text, discourses are continually appropriated by new legal actors who subject them to "de-" and "recontextualization" (Bauman and Briggs, 1991), as they insert these discourses in their new textual environment-a process that goes hand in hand with subtle transformations that may nevertheless have strong legal consequences and that are open to strategic manipulation (for some particularly vivid examples, consider Matoesian, 2001;Ehrlich, 2007;Haket, 2007).…”
Section: Intertextuality In the Legal Processmentioning
confidence: 99%